ANALISIS PENERAPAN METODE WEIGHTED PRODUCT WP UNTUK PENILAIAN KELAYAKAN KREDIT KENDARAAN BERMOTOR - Damal Lihan; Budi Santoso; Andri Krisna Wijaya (Elkom: Jurnal Elektronika dan Komputer, 2026)
In the credit approval process, prospective customers are first surveyed, after which the Credit Analyst determines whether they are eligible to receive credit. A Credit Analyst is required to work quickly and accurately when analyzing the large number of incoming credit applications. As a result, the possibility of human error cannot be ignored, such as calculation errors, data misinterpretation, and other mistakes. Therefore, to support the decision-making process in determining customer creditworthiness, a computer-based system is needed to facilitate data analysis, evaluate credit applicant criteria, and process data into meaningful information for making decisions regarding semi-structured problems. A Decision Support System (DSS) is an appropriate solution to assist in the selection of motor vehicle credit applicants. The system is designed using the Weighted Product (WP) method, which is one of the methods in Fuzzy Multiple Attribute Decision Making (FMADM). The WP method was chosen because the criteria weighting calculations are relatively simple and not overly complex. The proposed system is expected to assist in the selection of credit applicants, thereby accelerating the credit evaluation process and reducing errors in determining customer creditworthiness. With the implementation of this system, Credit Analysts can more easily identify customers who are eligible to receive motor vehicle credit. In addition, the calculation process for determining the most suitable customers becomes easier and faster. The system also helps management reduce difficulties in selecting the best customers by considering and representing each evaluated criterion, resulting in accurate and reliable decisions.